EVALUATION AND COMPARISON OF ANXIOLYTIC ACTIVITY OF ETHANOLIC AND AQUEOUS LEAF EXTRACTS OF CALOPHYLLUM INOPHYLLUM IN ALBINO WISTAR RATS - ASRA BEGUM; MIRZA DANISH BAIG; SYED BASHEER UDDIN; A. VENKATESHWARA REDDY (International Journal of Pharma and Bio Sciences, 2014)
The aim of the present study was to perform phytochemical screening, acute oral toxicity and to evaluate and compare the anxiolytic activity of ethanolic and aqueous leaf extracts of Calophyllum inophyllum on albino wistar rats. Elevated plus maze method and Light and Dark model were implemented to determine the anxiolytic activity of the leaf extracts. Ethanolic and aqueous leaf extracts were administered orally. Acute oral toxicity studies were conducted using the OECD guidelines 423 Annexure – 2d. The results indicate the mortality was not observed during the acute oral toxicity studies and maximum safe does determined. The anxiolytic activity effect of the extracts showed that Calophyllum inophyllum leaf ethanolic extract doses 200mg/kg, 400mg/kg b.w and Calophyllum inophyllum leaf aqueous extract dose 400mg/kg b.w exhibited significant anxiolytic activity whereas Calophyllum inophyllum leaf aqueous extract dose 200mg/kg b.w did not show any significant activity. Additionally, the effects were more prominent in the ethanolic extract than the aqueous extract which may be due to successive solvent extraction.